DEVELOPMENT OF STUDENTS’ RESEARCH SKILLS THROUGH DATA PROVIDED DURING THE STUDY OF THE DISCIPLINE - Kurmanali Guldana Kuantkanovna (Interdisciplinary Science Studies, 2025)
This research was inspired by the researchers’ curiosity to identify how learners’ can become more independent and constructive as a result their engagement with experimental practical works and thus develop research skills from chemistry and mathematics classroom activities. According to the researchers’ (who happen to be current chemistry teachers at Nazarbayev Intellectual School of Physics and Mathematics, Kokshetau Kazakhstan) classroom experiences, they strongly believe that students’ learning achievement improves if they are exposed to practical experiments because this will grant students more opportunity to become constructivists. During the research, they randomly selected 12 grades 8 and 9 students who are both boys and girls as the focused group. The students are of the ages ranging between 15 to 15 years. These students were put in a classroom to answer a questionnaire of 10 questions about the chemistry and mathematics lessons as part of the survey. 59% feel there is a need for teachers’ assistance and support in order to construct their own learning during classroom activities such as lab work while 34% of this focused group claim that they solely rely on information from the teacher; meaning they cannot construct their own words. There was also an observation on how their learning activities go on in a classroom as the teachers delivers instructions. The students were given questions to answer in order to increase their curiosity and engagement